Differences in College Lecturers’ Ratings of Principals Instructional Leadership: A Jamaican Perspective. - Nevins-Bennett, Cerease (Future Science / FSH-PH Publications, 2023)
The purpose of this quantitative study is to determine how lecturers rated their principals as instructional leaders and to examine the differences in lecturers’ ratings of principals’ instructional leadership based on the demographic characteristics of gender, age range, lecturing status, number of years current principals have been employed to the colleges. and the highest level of educational attainment of the current principals. A survey that adopted the Principal Instructional Management Rating Scale (PIMRS) was used to collect data from 170 participants purposively. Overall, lecturers had moderately high ratings of principals’ instructional leadership within the colleges. There were no statistically significant differences in the ratings of lecturers based on age range and the number of years the current principal has been employed within the colleges. Male lecturers rated their principal higher than female lecturers on the dimension of creating a positive college climate. Adjunct lecturers gave their principals a higher rating than full-time lecturers on the dimension of managing instructional programs. Principals that had a master’s degree as their highest educational attainment were rated higher by the lecturers on the dimension of defining the college mission. This study contributes to the body of knowledge by filling the gap at the college level.